1996
DOI: 10.1099/00222615-45-5-319
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a model of penicillin-resistant Streptococcus pneumoniae pneumonia in healthy CBA/J mice

Abstract: Examination of strain differences in the susceptibility of mice to experimental respiratory tract infection with penicillin-resistant Streptococcus pneumoniae TUM19 revealed that a fatal infection model could be induced in immunocompetent CBA/J mice, but not in C3H/HeN, C57BL/6 or ICR mice. After intranasal instillation of c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…The infection produced in the 24-h BAP model was confined to the interior of the airway, with no notable tissue disruption and minimal inflammatory response [14]. Importantly, the epithelial lining of the airspace remained intact and largely unperturbed.…”
Section: Resultsmentioning
confidence: 99%
“…The infection produced in the 24-h BAP model was confined to the interior of the airway, with no notable tissue disruption and minimal inflammatory response [14]. Importantly, the epithelial lining of the airspace remained intact and largely unperturbed.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for the existence and efficacy of phosphocholine antibodies indicates that they may play an important role in the innate immune response (11,17,32). However, a number of authors have indicated that the genetic background of CBA mice renders this murine strain susceptible to pneumococcal infection and that this finding cannot be accounted for by the xid locus only but must involve the abrogating effect of hitherto unknown genes (8,10,26).…”
mentioning
confidence: 99%
“…Five-week-old male CBA/J specific-pathogen-free mice (body weight, 20 g) were purchased from Charles River Japan. The CBA/J mouse model of PRSP pneumonia has been described previously (19,21). All mouse experiments were performed according to the guidelines of the Laboratory Animal Center for Biomedical Research, Nagasaki University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%